2012
DOI: 10.1007/s00464-012-2345-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy in adult and pediatric obese patients: a comparative study

Abstract: Laparoscopic sleeve gastrectomy in the pediatric age group is of similar safety and effectiveness compared with adults. Pediatric patients had fewer major complications and were more compliant with follow-up than adults. Nevertheless, long-term results are required to further clarify the safety and effectiveness of LSG in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 39 publications
3
33
0
1
Order By: Relevance
“…It has been previously reported that children and adolescents who undergo laparoscopic sleeve gastrectomy (LSG) experience well-tolerated, effective, and sustained reduction of body weight, with resolution of the majority of their co-morbidities [7][8][9]. However, offering bariatric surgery to patients with syndromic forms of obesity, let alone PWS, is still controversial [10].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been previously reported that children and adolescents who undergo laparoscopic sleeve gastrectomy (LSG) experience well-tolerated, effective, and sustained reduction of body weight, with resolution of the majority of their co-morbidities [7][8][9]. However, offering bariatric surgery to patients with syndromic forms of obesity, let alone PWS, is still controversial [10].…”
mentioning
confidence: 98%
“…[2][3][4][5][6][7][8][9][10][11][12][13]. This syndrome has an estimated prevalence ranging from 1 in 8,000 to 1 in 50,000 individuals.…”
mentioning
confidence: 99%
“…This technique involves the removal of a large portion of the stomach through a vertical resection, and the remaining stomach has a volume drastically reduced, with a capacity of around 100/150 ml. Weight loss outcomes in some study were similar between pediatric and adult patients at all time points, suggesting that LSG is similarly safe and effective in young and adult patients through at least 1 year of follow-up [192].…”
Section: Treatment Options In Patients With Genetic Obesitymentioning
confidence: 79%
“…Bariatric surgery is the only effective intervention to achieve substantial long-term weight loss and improvement of comorbidities 1,2 in adults. With the increasing prevalence of childhood and adolescent obesity [3][4][5] and their related health risks both at current age [6][7][8] as well as later in life, 4,9 early treatment is of major importance and morbidly obese adolescents are increasingly being considered for bariatric surgery. However, there is controversy regarding the ethics of bariatric surgery in adolescents, with questions on long-term safety and effectiveness of bariatric surgery in adolescents remaining unanswered.…”
Section: Introductionmentioning
confidence: 99%